(untitled) (Research, Society and Development, 2020)
The agricultural industry is the main emitter of methane (CH4) and nitrous oxide (N2O), gases that each have a global warming potential that is greater than that of CO2 by 23 and 298 times, respectively. On a global scale, enteric fermentation from ruminant animal production (especially of cattle and sheep) is responsible for between 21% and 25% of total anthropogenic CH4 emissions. The search for effective, simple, and fast methods to measure the production of CH4 and other products from ruminal fermentation has been the objective of several studies on ruminant nutrition. Thus, techniques have been developed under experimental conditions of Brazil and other international countries to quantify CH4 emissions of ruminants. The objective of this literature review is to discuss and compare the existing techniques of measuring enteric CH4 from ruminants. Each technique has a shortcoming or disadvantage in its characterization of ruminal fermentation. The ex-situ technique of measuring CH4 from ruminal fermentation has been quite promising, because it facilitates the measurement of CH4 and other fermentation products, such as short chain fatty acids (SOFA). CH4 detection by a portable laser is effective in monitoring fluctuations in emission and is recommended especially for short-term measurements of respiring and eructating animals reared in a feedlot system. Other methods are being improved and better adapted for practical use in the ongoing quest for more efficient uses of ruminal fermentation products.